Myths in How to Train your Dragon (2025) Film: Barthesian Semiotic Reading - Rini, Ika Puspita; Amalia, Syahara Dina (Universitas Muhammadiyah Surakarta, 2025)
Purpose: This study discusses how myths are represented in the film How to Train Your Dragon (2025) based on Barthes' Semiotic Analysis Model and how the myths affect the characters in the film. Methodology: This research is qualitative descriptive study with subject is the live-action film How to Train Your Dragon and the object is scenes related to myths in the film, with the data collected through intensive scene documentation and purposively selected based on thematic, narrative, and symbolic relevance, then analyzed using Barthes' Semiotics Analysis Model at the levels of denotation, connotation, and myth.Results: The result of the study shows that this film constructs interrelated myths about responsibility-based leadership, the importance of empathy in human relationships with other creatures, and a shift in values from conflict to cooperation. In addition, these myths also affect character development, as seen in Hiccup's increasingly empathetic moral changes, the trusting relationship between him and Toothless, and Stoick's efforts to balance traditional values with new values.Applications/Originality/Value: Future researchers can examine the same film with a more specific focus on educational values such as empathy, moral courage, and cooperation, or explore the representation of myths in other films and learn how these myths can be used as a medium for teaching moral values in a community.